Gereja Yang Elastis Sebagai Model Bergereja di Era Digital - Yudha Nugraha Manguju (BIA': Jurnal Teologi dan Pendidikan Kristen Kontekstual, 2022)
Abstract: The church in the 21st century is undergoing such great development and change. This is due to the Industrial Era 4.0 which is marked by advances in digital technology and the COVID-19 pandemic which requires churches to rethink their ministry models in the digital space. The Church has entered a new era in the pattern of its ministry mediated by digital technology. This study aims to find models of churches that are emerging in the digital age by utilizing the idea of a liquid church in Pete Ward's thinking as a development of the new character of the church. The research method used is qualitative with a literature study and interview approach. This research shows that the face of the church in the digital era can be distinguished into four models, namely Analog Church, Digilog Church or Phygital Church, E-Church and Virtual Reality Church. The new characteristics offered in this paper are the "Elastic Church" as a model of church in the digital era which can be understood in three aspects, namely the church as a network-participatory community, a resilient-adaptive community, and a missional-inspirational community.Â Keywords: Digital Church, Ecclesiology, Â Liquid Church, Elastic Church, Pete Ward. Â Abstrak: Gereja di abad 21 mengalami perkembangan dan perubahan yang begitu besar. Hal ini disebabkan oleh Era Industri 4.0 yang ditandai dengan kemajuan teknologi digital yang mengharuskan gereja untuk memikirkan kembali model pelayanannya di ruang digital. Gereja telah memasuki era baru dalam corak pelayanannya yang distimulasi oleh teknologi digital. Penelitian ini bertujuan untuk menemukan model-model gereja yang muncul di era digital dengan memanfaatkan gagasan gereja cair dalam pemikiran Pete Ward sebagai pengembangan karakter gereja yang baru. Metode penelitian yang digunakan adalah kualitatif dengan pendekatan studi pustaka. Penelitian ini memperlihatkan bahwa wajah gereja di era digital sebagai dapat dibedakan menjadi empat model, yakni Analog Church, Digilog Church atau Phygital Church, E-Church dan Virtual Reality Church.Â  Karakteristik baru yang ditawarkan dalam tulisan ini yaitu â€œGereja Elastisâ€ sebagai model bergereja di era digital yang dapat dipahami dalam tiga aspek, yakni gereja sebagai komunitas jejaring-partisipatif, komunitas resiliensi-adaptif dan komunitas misional-inspiratif.Â Kata Kunci: Eklesiologi, Gereja Cair, Gereja Digital, Gereja Elastis, Â Pete Ward.